Gender and breeding postdoctoral fellow initiative - McDougall, Cynthia (WorldFish, 2017)
Presented by Cynthia McDougall (World Fish), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017